Marshmallow Test: Understanding self-control and how to master It - Mischel, Walter (London Transworld publishers, 2014)
The Marshmallow Test A child is presented with a marshmallow and given a choice: Eat this one now, or wait and enjoy two later. What will she do? And what are the implications for her behaviour later in life? Walter Mischels now iconic marshmallow test, one of the most famous experiments in the history of psychology, proved that the ability to delay gratification is critical to living a successful and fulfilling life: self-control not only predicts higher marks in school, better social and cognitive functioning, and a greater sense of self-worth; it also helps us manage stress, pursue goals more effectively.
Keywords: Self control; Will power; Psychology